Macroeconomic Effects From Government Purchases and Taxes * - Barro, Robert J.; Redlick, Charles J. (Quarterly Journal of Economics, 2011)
For U.S. annual data that include World War II, the estimated multiplier for temporary defense spending is 0.4–0.5 contemporaneously and 0.6–0.7 over 2 years. If the change in defense spending is “permanent” (gauged by Ramey's defense news variable), the multipliers are higher by 0.1–0.2. Since all estimated multipliers are significantly less than 1, greater spending crowds out other components of GDP, particularly investment. The lack of good instruments prevents estimation of reliable multipliers for nondefense purchases; multipliers in the literature of two or more likely reflect reverse causation from GDP to nondefense purchases. Increases in average marginal income tax rates (measured by a newly constructed time series) have significantly negative effects on GDP. When interpreted as a tax multiplier, the magnitude is around 1.1. The combination of the estimated spending and tax multipliers implies that the balanced-budget multiplier for defense spending is negative. We have some evidence that tax changes affect GDP mainly through substitution effects, rather than wealth effects.